Knockout or inhibition of DHPS suppresses ovarian tumor growth and metastasis by attenuating the TGFβ pathway - Guannan Zhao; Xinxin Zhao; Ziping Liu; Baojin Wang; Peixin Dong; Hidemichi Watari; Lawrence M. Pfeffer; Gabor Tigyi; Wenjing Zhang; Junming Yue (Scientific Reports)
Abstract Deoxyhypusine synthase (DHPS) is an enzyme encoded by the DHPS gene, with high expression in various cancers, including ovarian cancer (OC). DHPS regulates the translation initiation factor EIF5A, and EIF5A2 knockout inhibits OC tumor growth and metastasis by blocking the epithelial-to-mesenchymal transition (EMT) and the TGFβ pathway. In this study, we show that DHPS is amplified in OC patients, and its elevated expression correlates with poor survival. Using lentiviral CRISPR/Cas9 vectors for DHPS knockout, we observed EMT inhibition in SKOV3 and OVCAR8 cells through suppressed hypusination and reduced EIF5A2 expression. Inhibition of DHPS activity with GC7 similarly blocked hypusination and EMT. Disrupting DHPS expression, either genetically or pharmacologically, inhibited primary tumor growth and metastasis in OC mouse models. These findings suggest that targeting DHPS and inhibiting hypusination could be promising strategies for OC treatment.